Associations of Receptor for Advanced Glycation End Products -374 T/A and Gly82 Ser and Peroxisome Proliferator-Activated Receptor Gamma Pro12Ala Polymorphisms in Turkish Coronary Artery Disease Patients - (:unkn) unknown (MARY ANN LIEBERT, INC, 2012)
Aim: The aim of the present study was to investigate the individual and combined effects of receptor for advanced glycation end products (RAGE) -374T/A, RAGE Gly82Ser, and peroxisome proliferator-activated receptor gamma (PPAR-gamma) Pro12Ala polymorphisms on the development of coronary artery disease (CAD). Materials and Methods: This study was carried out in 87 patients with CAD and 52 CAD-free healthy controls. Polymerase chain reaction, restriction fragment length polymorphism, and agarose gel electrophoresis techniques were used to determine RAGE -374T/A, RAGE Gly82 Ser, and PPAR-gamma Pro12 Ala. Results: Individual allele and genotype frequencies of RAGE -374T/A, RAGE Gly82Ser, and PPAR-gamma Pro12Ala polymorphisms were not significantly different between study groups. However, compared with the control group, wild-type T allele frequency was found to be higher in patients with diabetes (p = 0.009). To investigate the combined effects of RAGE and PPAR polymorphisms, haplotype analysis was elevated and there was no statistical difference between the haplotypes of RAGE Gly82Ser with RAGE-374T/A or PPAR Pro12Ala. However, the frequency of RAGE-374T/PPAR12Ala haplotype was found to be higher in both the patient group (p = 0.024) and in patients without diabetes (p = 0.037). Conclusion: The results of the present study demonstrated that possessing the A allele of RAGE -374T/A polymorphism by diabetic CAD patients and possessing the-374T/A1a12 haplotype of RAGE -3741/A and PPAR-gamma Pro12 Ala polymorphisms by the patients group were the most important risk factors for CAD.
Keywords: CARDIOVASCULAR-DISEASE; RAGE GENE; DIABETES-MELLITUS; INFLAMMATION; ATHEROSCLEROSIS; PROMOTER; PPARG; RISK; AGES